Mental Representation of Arm Motion Dynamics in Children and Adolescents - Crognier, Lionel (Public Library of Science, 2013)
Motor imagery, i.e., a mental state during which an individual internally represents an action without any overt motor output, is a potential tool to investigate action representation during development. Here, we took advantage of the inertial anisotropy phenomenon to investigate whether children can generate accurate motor predictions for movements with varying dynamics. Children (9 and 11 years), adolescents (14 years) and young adults (21 years) carried-out actual and mental arm movements in two different directions in the horizontal plane: rightwards (low inertia) and leftwards (high inertia). We recorded and compared actual and mental movement times. We found that actual movement times were greater for leftward than rightward arm movements in all groups. For mental movements, differences between leftward versus rightward movements were observed in the adults and adolescents, but not among the children. Furthermore, significant differences between actual and mental times were found at 9 and 11 years of age in the leftward direction. The ratio R/L (rightward direction/leftward direction), which indicates temporal differences between low inertia and high inertia movements, was inferior to 1 at all ages, except for the mental movements at 9 years of age, indicating than actual and mental movements were shorter for the rightward than leftward direction. Interestingly, while the ratio R/L of actual movements was constant across ages, it gradually decreased with age for mental movements. The ratio A/M (actual movement/mental movement), which indicates temporal differences between actual and mental movements, was near to 1 in the adults' groups, denoting accurate mental timing. In children and adolescents, an underestimation of mental movement times appeared for the leftward movements only. However, this overestimation gradually decreased with age. Our results showed a refinement in the motor imagery ability during development. Action representation reached maturation at adolescence, during which mental actions were tightly related to their actual production.